2015
DOI: 10.1111/trf.13300
|View full text |Cite
|
Sign up to set email alerts
|

Full‐length nucleotide sequences of 30 common SLC44A2 alleles encoding human neutrophil antigen‐3

Abstract: Background HNA-3a alloantibodies can cause severe transfusion-related acute lung injury (TRALI). The frequency of the single nucleotide polymorphisms (SNPs) indicative of the two clinically relevant HNA-3a/b antigens are known in many populations. In the present study, we determined the full length nucleotide sequence of common SLC44A2 alleles encoding the choline transporter-like protein-2 (CTL2) that harbors HNA-3a/b antigens. Study design and methods A method was devised to determine the full length codin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…The HNA‐3a/b SNP (461G>A) was detected by both sequencing approaches (Table ). In addition, we detected the two known SNPs 503‐15T>C (rs1560711) located in Intron 7 in Yi and Tibetan populations and 331‐44G>A (rs12972963) located in Intron 5 in the Han population (Table ) . The only other known SNP in these DNA stretches, 457C>T (rs147820753), was not found in the three populations.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The HNA‐3a/b SNP (461G>A) was detected by both sequencing approaches (Table ). In addition, we detected the two known SNPs 503‐15T>C (rs1560711) located in Intron 7 in Yi and Tibetan populations and 331‐44G>A (rs12972963) located in Intron 5 in the Han population (Table ) . The only other known SNP in these DNA stretches, 457C>T (rs147820753), was not found in the three populations.…”
Section: Resultsmentioning
confidence: 90%
“…In addition, we detected the two known SNPs 503‐15T>C (rs1560711) located in Intron 7 in Yi and Tibetan populations and 331‐44G>A (rs12972963) located in Intron 5 in the Han population (Table ) . The only other known SNP in these DNA stretches, 457C>T (rs147820753), was not found in the three populations. The SNPs detected in the study were in a Hardy‐Weinberg equilibrium (p > 0.05), with the exception of one SNP pair (503‐15T>C and 461G>A) in the Yi population (p = 0.049).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…These differences are sufficient to create the HNA3a epitope. In support of subtle changes having an effect on protein conformation, Chen et al 28 and Flesch et al 29 report a missense SNP rs147820753 position 537C>T (p1) p.151 leu>phe which immediately precedes rs2288904 and alters HNA-3a antibody reactivity with the epitope involving p.152 arg .…”
Section: 0 Discussionmentioning
confidence: 99%
“…If the proteins from both alleles are expressed in heterozygous individuals and the resulting molecules combine to form a transporter molecule, different folding of the protein containing arginine and the protein containing glutamine at amino acid 152/154 could result in altered function of the complex. Although Chen et al 28 reported that computational predictions of the p.154 arg and p154 gln alleles revealed no deleterious structural or functional differences, this type of analysis does not take into account the subtle conformational change that result from these different amino acids. These differences are sufficient to create the HNA3a epitope.…”
Section: 0 Discussionmentioning
confidence: 99%